The microbiota-gut-brain axis in stress and depression - Tan, Hwei-Ee (Frontiers in Neuroscience, 2023)
Humans and animals are evolved to have instinctive physiological responses to threats. The perception of threat by the brain triggers a multitude of changes across the brain and body. A large body of research have demonstrated that our hardwired survival instinct, the stress response, can become maladaptive and promote major depressive disorders and other neuropsychiatric impairments. However, gaps in our understanding of how chronic stress contributes to depression and mental disorders suggest that we also need to consider factors beyond the biology of the host. The unravelling of the structure and function of microorganisms that humans and animals are host to have driven a paradigm shift in understanding the individual as a collective network composed of the host plus microbes. Well over 90% of bacteria in the body reside in the large intestines, and these microbes in the lower gut function almost like an organ in the body in the way it interacts with the host. Importantly, bidirectional interactions between the gut microbiota and the brain (i.e., the two-way microbiota-gut-brain axis) have been implicated in the pathophysiology of mental disorders including depression. Here, in summarizing the emerging literature, we envisage that further research particularly on the efferent brain-gut-microbiota axis will uncover transformative links in the biology of stress and depression.